2019
DOI: 10.3389/fneur.2019.00124
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mouse Tauopathy Model for Repetitive Mild Traumatic Brain Injury: Evaluation of Long-Term Effects on Cognition and Biomarker Levels After Therapeutic Inhibition of Tau Phosphorylation

Abstract: Traumatic brain injury (TBI) is a risk factor for a group of neurodegenerative diseases termed tauopathies, which includes Alzheimer's disease and chronic traumatic encephalopathy (CTE). Although TBI is stratified by impact severity as either mild (m), moderate or severe, mTBI is the most common and the most difficult to diagnose. Tauopathies are pathologically related by the accumulation of hyperphosphorylated tau (P-tau) and increased total tau (T-tau). Here we describe: (i) a novel human tau-expressing tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 119 publications
1
33
0
1
Order By: Relevance
“…Repetitive mild TBI also cause cognitive impairment in mice as it was shown in the MWM test 2 months after TBI [23]. Few studies have reported chronic deficits following experimental repetitive mild TBI [12], [24], [25], lasting up to 12 months after injury in a mouse model [26]. Similar to these studies, in our study, we confirmed that repetitive mild TBI results in long-term cognitive impairment, even when the injury was caused by a very small impact.…”
Section: Behavioural Alterationssupporting
confidence: 90%
“…Repetitive mild TBI also cause cognitive impairment in mice as it was shown in the MWM test 2 months after TBI [23]. Few studies have reported chronic deficits following experimental repetitive mild TBI [12], [24], [25], lasting up to 12 months after injury in a mouse model [26]. Similar to these studies, in our study, we confirmed that repetitive mild TBI results in long-term cognitive impairment, even when the injury was caused by a very small impact.…”
Section: Behavioural Alterationssupporting
confidence: 90%
“…There is growing interest in the role of tau in post-TBI neurodegeneration, and the idea that targeting pathological tau may point to a therapeutic opportunity in TBI is growing [13,[42][43][44]. The C. elegans model of tau TBI toxicity described here could be employed to rapidly screen TBI conditions involving the generation of potentially toxic tau species in both experimental and human TBI, to investigate the mechanisms underpinning chronic neurodegeneration in TBI, and to develop a high-throughput experimental platform to screen for pharmacological agents that interfere with TBI-associated tau toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing interest in the role of tau in post-TBI neurodegeneration, and the idea that targeting pathological tau may point to a therapeutic opportunity in TBI is growing 13,[33][34][35] .…”
Section: Discussionmentioning
confidence: 99%